Corpus of the Muslim Coins of Bengal : (Down to AD 1538) - Karim, Abdul (Brill | Manohar Publishers & Distributors, 2024)
Bengal in the medieval period came to be ruled by the Muslim Sultans with the establishment of Bakhtiyar Khalji (r. 1203-1206). Apart from official and non-official literature and archaeological findings, numismatic studies too plays a very important role in understanding the socio-economic and political history of any region, nation, or confederation of states. In this book, we find that it is in Bengal the collection and publication of coins minted under the Muslim Sultans during the Delhi Sultanate and independent Sultanates, in the various museums and libraries. The book is divided into two major parts, one is the critical analysis of coins and the other is the study of coins issued by Muslim dynasts of Bengal. The first part covers the coins minted from the time of Sultan Iltutmish till Muhammad bin Tughluq. It also covers the coins issued by the Bengal governors under the rule of the Delhi Sultans. This section also covers the analysis of coins from Sultan Ghiyas-ud-Din Iwad Khalji (r. 1533-1538) of the Hussain Shahi Sultanate, who was defeated by Sher Shah Suri (r. 1537- 1545). The second part of this book covers the issues concerning the numismatic studies done with the help of tables and places made by the author. These include the following: a chronological survey of Bengal Sultan coins, the minting process, and popular Islamic titles issued, which include the famous Arabic-Persian titles, such as 'Khilafat' and 'Khilafat Allah', and the coins issued by princes and non-rulers. Interestingly, this part ends by covering the inscribed names of the Abbasid Caliphs and zamindars under the Muslim Sultans, such as Raja Ganesha and Raja Mahendra Deva.